PENGARUH RASIO KEUANGAN EARLY WARNING SYSTEM TERHADAP HARGA SAHAM PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010- 2014 - Aneu Kuraesin; Rina Permatasari (SENTIA 2016, 2016)
The problems discussed in this study is whether the Financial Ratios Early Warning System which consists of Incurred Loss Ratio, Liabilities of Liquidity Assets Ratio, Agent'sBalance to Surplus Ratio, and Premium Growth Ratio effect simultaneously and partially onStock Price. This study aims to analyze financial ratios EWS in the formation of thecompany's stock price insurance listed in Indonesia Stock Exchange (BEI) period 2010-2014.The population in this research are all insurance companies listed in Indonesia StockExchange period 2010-2014 and used sample 10 of 11 companies listed by using purposivesampling method. The method used is descriptive method verification. The data used in thisresearch is secondary data, bycollecting from the audited financial statements and publishedwithin the period of observation that is downloaded from the website www.idx.co.id. Theanalysis technique used in this research is multiple linear regression, hypothesis testing, andthe coefficient of determination.The results showed that the Financial Ratios Early Warning System, comprised of Incurred Loss Ratio, Liabilities of Liquidity Assets Ratio, Agent's Balance to Surplus Ratio, and Premium Growth Ratio simultaneously significant effect on stock price of 4.433 with a significance level 0,04≤0,05 . Partially Claims Expense Ratio and Liquidity Ratios significantly affect the stock price while the ratio of Agents ' Balance to Growth Ratio Surplus and premiums do not significantly affect the stock price